Prospective Scenarios of Corporate Universities in Brazil - 2030 - Spada, Eduardo Spada; Arruda Cavalcante Forte, Sergio Henrique (Future Studies Research Journal: Trends and Strategies, 2018)
In a highly competitive environment, personal skills development for businesses is a key factor to ensure the continuous success of the organizations. For this reason, Brazilian public and private institutions have sought to stimulate and invest in vocational education, employee skills, and institutional partnerships. This study involves the development of prospective scenarios for corporate universities in Brazil over the next 13 years (2017-2030), to subsidize the Brazilian organizations to deal with any of such scenarios in the best way possible, or even to create favorable conditions for them. A qualitative and descriptive research was carried out by using a survey submitted to a group of four researchers and 15 expert in Corporate Education or executives from UCs, according to the proposed model, having been identified 16 variables for the construction of prospective scenarios for Brazilian Corporate Universities, in which 15 of them belongs to the optimistic/realistic scenarios and only one of them to the pessimistic one, making it possible to compose their strategies in medium and long terms, reducing vulnerabilities for Corporate Universities.